Bilateral Cooperation between Philippines and the United States of America in Counterterrorism against ISIS and Abu Sayyaf Group - Qeisha Firmansyah; Wibowo, Prihandono (Global Local Interactions: Journal of International Relations, 2024)
Philippines is confronted with a number of security challenges that pose a threat to the country and its inhabitants. Among these challenges are the threat of terrorism. The objective of this research is to ascertain the manner in which the government responds to the ISIS movement within its territory, specifically through the bai'at relationship with the Abu Sayyaf group in Philippines. The liberal rationale of Immanuel Kant and the methods of counterterrorism and multilateralism inform the counterterrorism effort, which is designed to address and overcome terrorist disruptions from separatist groups and to prevent and respond to further terrorist attacks in order to fulfill the obligation to maintain the security of its people. As a member of the United Nations (UN), Philippines reaffirms its commitment to prevent, suppress, and counter all forms of terrorism under the UN Charter, Declarations, and relevant international laws. The Philippine government's efforts, policies, and programs demonstrate that achieving counterterrorism objectives will be challenging due to the lack of a deterrent effect on perpetrators. This is because the criminalization of terrorism perpetrators is often associated with human rights, which has been a topic of discussion among people and communities who believe that the punishment given to terrorism perpetrators should also be based on the values of human rights.